Anti-inflammatory and anti-apoptotic potential of beta-glucan on chemotherapy-induced nephrotoxicity in rats: β-glucan on cyclophosphamide-induced nephrotoxicity - Ozcan Metin, Tuba; Turk , Ahmet; Yalcın , Alper; Adanır , Ilkay (Journal of Surgery and Medicine, 2023)
Background/Aim: Cyclophosphamide (CP) is an anti-cancer agent that mediates nephrotoxicity. Beta (β)-glucan has restorative effects on kidney toxicities through its antioxidant potential; however, the effects of β-glucan on CP-induced renal injury remain unknown. In an experimental nephrotoxicity model using rats, we sought to examine the potential protective action of β-glucan on kidney histomorphology, apoptosis, and TNF-α expression. Methods: Male albino Wistar rats were divided equally into four groups: control, CP, β-glucan, and CP+β-glucan. The kidney tissues of the rats were examined for TNF-α and caspase-3 immunostaining to evaluate inflammation and apoptosis, respectively. Hematoxylin and eosin (H&E) and periodic acid–Schiff (PAS) staining were used for histopathological analyses. Results: The CP group showed severe histopathological damage in the renal tissues of rats. In the renal tissue of the CP group, immunoreactivities for TNF-α (1.25 [0.079] and caspase-3 (1.506 [0.143] were also higher than the control group (0.117 [0.006] and 0.116 [0.002], respectively; P<0.001). In the CP+β-glucan group, the histopathological changes significantly improved. Conclusion: Beta-glucan has therapeutic potential against CP-induced nephrotoxicity in rat kidney.